Adiposity, cardiovascular, and health-related quality of life indicators and the reallocation of waking movement behaviors in preschool children with overweight and obesity: An isotemporal data analysis - Dooley, Erin E.; Pettee Gabriel, Kelley; Kohl, Harold W.; Durand, Casey P.; Hoelscher, Deanna M.; Byrd-Williams, Courtney E. (PloS one, 2020)
Isotemporal substitution evaluates hypothetical time replacement scenarios of physical movement on health, with few studies conducted among ethnically diverse preschool-aged populations. This study examines the reallocation of waking movement behaviors on adiposity, cardiovascular, and quality of life indicators among low-income, majority Hispanic preschool-aged youth (2-5 years) with overweight. Participants wore an ActiGraph monitor (waist) and completed adiposity, cardiovascular, and health-related quality of life health assessments. Covariates included age, sex, ethnicity, and socioeconomic status. The isotemporal substitution approach was employed to address study aims. Complete data were available for 131 preschoolers. For boys, reallocating 5 minutes of stationary time with light intensity, moderate to vigorous intensity, or total physical activity showed a relation with beneficial reductions in adiposity indicators; for girls, these relations were statistically null. For boys and girls, reallocating 5 minutes of stationary time [-2.2 (95% CI: -3.7, -0.7) mmHg], light intensity [-2.1 (95% CI: -3.7, -0.7) mmHg], or moderate intensity activity [-2.7 (95% CI: -5.0, -0.4) mmHg] to vigorous intensity activity was related to favorable systolic blood pressure. Reallocating 5 minutes of stationary time to moderate to vigorous intensity activity [0.6 (95% CI: -1.0, -0.1) mmHg] or total physical activity [-0.2 (95% CI: -0.3, -0.01) mmHg] was related to lowered systolic blood pressure. Reallocating 5 minutes of stationary time to moderate to vigorous intensity activity [0.6 (95% CI: -1.1, -0.02) bpm] was related to lowered resting heart rate. No significant results for quality of life were found. Reallocation of time from stationary time to other movement behaviors is associated with several favorable adiposity and cardiovascular health outcomes among preschool children with overweight and obesity.